Martyrdom in Modern Islam - Showkat Ahmad Dar (International Institute of Islamic Thought, 2015)
Meir Hatina, associate professor of Islamic and Middle Eastern studies and director of the Levtzion Center for Islamic studies at the Hebrew University of Jerusalem, explores the evolving perceptions of martyrdom in modern times and their relevance on past legacies in both Sunni and Shi‘i milieus. He also makes comparative references to Judaism, Christianity, and other non-Islamic cultures. The book is divided into eight chapters, an introduction, a conclusion, a bibliography, and an index. In the introduction the author discusses the manifestations of martyrdom throughout history, its definitions, socio-political implications, and importance in various world religions. In order to present this concept’s historical evolution and notions and how it is an effective tool for forming and reinforcing groups, Hatina has framed his book in a series of well-arranged chapters. In the first chapter, “Defying the Oppressor: Martyrdom in Judaism and Christianity,” the author traces the historical and theological foundations of this phenomenon in both religions. He relates how traditional Jews were ready to sacrifice their life and viewed martyrdom as the highest degree of their love for God. However, he argues that with the advent of the Zionist movement, this readiness was replaced “by an activist approach to self-sacrifice for the national revival.” Christians, on the other hand, considered martyrdom “the key for salvation.” By quoting the remarks of Quintus Tertullian (d. c. 240), the father of Latin Christianity, namely, “your cruelty is our glory” and “the blood of the martyrs is the seed of the church” (p. 26), Hatina seeks to express the early Christians’ readiness to embrace their non-violent and defensive deaths at the hands of the pagan Romans. In chapter 2, “Dying for God in Islam,” Hatina delineates the evidence of martyrdom in Islamic texts and its diverse interpretations by renowned scholars. He mentions the two types of death in this regard – death for the cause of Allah and self-inflicted suicide – and cites the relevant fatwas of both Sunni and Shi‘i scholars. Denouncing any sort of self-inflicted suicide, including murder with reference to shar‘ī texts, he nevertheless appreciates the soldiers’ wish for death on the battlefield against their enemies. He presents martyrdom in Islamic legal thought as an exalted form of death and argues that theologians stressed that a soldier who desires such a death eventually finds a greater reward ...